A training goal-oriented categorization model of high-intensity interval training - Stöggl, Thomas L.; Strepp, Tilmann; Wiesinger, Hans-Peter; Haller, Nils (Frontiers in Physiology, 2024)
There are various categorization models of high-intensity interval training (HIIT) in the literature that need to be more consistent in definition, terminology, and concept completeness. In this review, we present a training goal-oriented categorization model of HIIT, aiming to find the best possible consensus among the various defined types of HIIT. This categorization distinguishes between aerobic and anaerobic energy contributions and concludes with six different types of HIIT derived from the literature, based on the interaction of interval duration, interval intensity and interval:recoverybreak ratio. We discuss the science behind the defined types of HIIT and shed light on the possible effects of the various types of HIIT on aerobic, anaerobic, and neuromuscular systems and possible transfer effects into competition performance. We highlight various research gaps, discrepancies in findings and not yet proved know-how based on a lack of randomized controlled training studies, especially in well-trained to elite athlete cohorts. Our HIIT toolbox approach is designed to guide goal-oriented training. It is intended to lay the groundwork for future systematic reviews and serves as foundation for meta-analyses.